2014
DOI: 10.1021/bi500571q
|View full text |Cite
|
Sign up to set email alerts
|

Variola Type IB DNA Topoisomerase: DNA Binding and Supercoil Unwinding Using Engineered DNA Minicircles

Abstract: Type IB topoisomerases unwind positive and negative DNA supercoils and play a key role in removing supercoils that would otherwise accumulate at replication and transcription forks. An interesting question is whether topoisomerase activity is regulated by the topological state of the DNA, thereby providing a mechanism for targeting the enzyme to highly supercoiled DNA domains in genomes. The type IB enzyme from variola virus (vTopo) has proven to be useful in addressing mechanistic questions about topoisomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Such discrepancies between experiments that employ excess enzyme over DNA and the reverse condition of excess DNA have been observed previously with hOGG1 14 and other enzymes. 36 The most likely explanation is that with excess DNA binding sites the target search time has become ratelimiting, which is supported by the observation that the presteady-state burst rate gradually increases as the hOGG1 concentration increases (Figure S1B and Table S1). In addition, our previous studies have indicated that the target search time of hOGG1 can be adversely affected by the presence of nonspecific DNA sequences.…”
Section: ■ Discussionmentioning
confidence: 87%
“…Such discrepancies between experiments that employ excess enzyme over DNA and the reverse condition of excess DNA have been observed previously with hOGG1 14 and other enzymes. 36 The most likely explanation is that with excess DNA binding sites the target search time has become ratelimiting, which is supported by the observation that the presteady-state burst rate gradually increases as the hOGG1 concentration increases (Figure S1B and Table S1). In addition, our previous studies have indicated that the target search time of hOGG1 can be adversely affected by the presence of nonspecific DNA sequences.…”
Section: ■ Discussionmentioning
confidence: 87%
“…In addition, several Type IB topoisomerases can cleave ribonucleotides incorporated in DNA ( 45 , 46 ), hinting that they may have RNA topoisomerase activity. Our screening showed that three Type IB DNA topoisomerases, human topoisomerase I (Top1) ( 47 ), human mitochondrial topoisomerase (Top1mt) ( 48 ), and Variola virus topoisomerase ( 49 ) failed to convert the RNA circle to knot (Supplementary Figure S2A-C). However, we cannot exclude the possibility that these enzymes may relax supercoiled dsRNA similar to their actions on dsDNA.…”
Section: Resultsmentioning
confidence: 99%
“…To prepare a duplex substrate containing a single-stranded DNA overhang, a region of the pMC454 plasmid ( 23 ) containing an Nt.BbvCI site and SalI site was amplified by PCR using oligonucleotide primers. Sequential digestion of the PCR product by SalI and Nt.BbvCI produced a 272 bp duplex with a 23 nt ssDNA 5′ overhang on one end.…”
Section: Methodsmentioning
confidence: 99%